The effect of 8 week resistance exercise on some anthropometric measurements and body composition to Sedentary Women - M. Turğut; S. Bağir; M. Sarikaya; Ü. Tinaz (Physical Education of Students, 2019)
Purpose: The aim of this study is to determine the effect of resistance exercise program applied to eight weeks on some anthropometric measurements and body composition in sedentary women. Material: Fifteen volunteer women with a mean age of 20.67 ± 1.29 years were included in the study. After asking the participants whether there are any health problems before the exercise program, detailed information was given and the exercises were implemented correctly and efficiently. Participants were given a 45-minute resistance exercise for 3 days a week. In order to compare the data obtained (Wilcoxon Test) was applied to compare descriptive statistics with pre- and post-exercise values via using SPSS 22.0. Before and after the exercise program (Weight, Hip circumference, calf circumference, chest circumference, waist circumference, shoulder circumference and BMI) were measured Results: According to the findings of the study, it was determined that there was a significant difference between the anthropometric measurement and body composition values of the exercise program applied before and after the exercise program of the participating women (p> 0.05) Conclusions: In conclusion, the effects of regularly performed exercises, especially aerobic and resistance exercises done for women, on persons are seen in the literature and research essays. Deterioration in the body composition of women is seen depending on age and excessive weight.